2016
DOI: 10.1097/pcc.0000000000000719
|View full text |Cite
|
Sign up to set email alerts
|

Parent Satisfaction With Communication Is Associated With Physician’s Patient-Centered Communication Patterns During Family Conferences*

Abstract: Objective To evaluate the association between physician’s patient-centered communication patterns and parental satisfaction during decision-making family conferences in the pediatric intensive care unit. Design Single-site, cross-sectional study. Setting Forty-four bed pediatric intensive care unit in a free-standing children’s hospital. Participants Sixty-seven English-speaking parents of 39 children who participated in an audio-recorded family conference with 11 critical care attending physicians. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
43
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(49 citation statements)
references
References 47 publications
5
43
1
Order By: Relevance
“…48 Parent-physician interactions with more patient-centered elements, such as increased proportions of empathetic statements, question asking, and emotional talk, positively influence parent satisfaction with care independent of the child’s severity of illness. 49 Parents of dying children also desire simple language in lieu of medical jargon. 47 High-quality communication at the end of a child’s life fosters trust between families and medical staff and helps to ensure that the dying child receives the best possible care.…”
Section: Discussionmentioning
confidence: 99%
“…48 Parent-physician interactions with more patient-centered elements, such as increased proportions of empathetic statements, question asking, and emotional talk, positively influence parent satisfaction with care independent of the child’s severity of illness. 49 Parents of dying children also desire simple language in lieu of medical jargon. 47 High-quality communication at the end of a child’s life fosters trust between families and medical staff and helps to ensure that the dying child receives the best possible care.…”
Section: Discussionmentioning
confidence: 99%
“…October et. al/ [31] advocate that parent satisfaction is largely associated with patient centered communication patterns during family conferences with the physician. In our study setting, most of the parents were not efficient in understanding English whereas the physician and nurses did not have Arabic as their primary language.…”
Section: Discussionmentioning
confidence: 99%
“…Our primary design was a retrospective review of de-identified transcripts from audio-recorded family-physician conferences in a single center PICU of a tertiary medical center. The audio-recordings were part of a larger study aimed at gaining a baseline understanding of family-physician communication during decision-making conferences (9). Eligible family-physician conferences included formal meetings during weekdays convened to discuss tracheostomy placement.…”
Section: Methodsmentioning
confidence: 99%